Perspektif Hukum Adat terhadap Kasus Jarimah Zina Berdasarkan Qanun Jinayat Aceh - Pakpahan, Firly Natasha; Andita, Naufalia; Tazkia, Rahma; Syauqi, Za’im Syaban (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Aceh is a province with special autonomy that implements customary law and Islamic Sharia in societal life, as regulated in “Article 1, Paragraph 2 of Law No. 18 of 2001”. Customary law in Aceh is an integral part of Indonesia's legal system, rooted in the traditions, culture, and Islamic values embraced by the Acehnese people. This law governs various aspects of life, some of which focus on community governance and Islamic criminal law. Within the context of Aceh's special autonomy, customary law is recognized and implemented alongside national law. With the coexistence of dual criminal law systems in Aceh, namely the Qanun Jinayat and the Indonesian Criminal Code (KUHP), it underscores the significant role of Islamic law in addressing criminal acts, including cases of adultery (zina). This article examines the implementation of customary law in Aceh that aligns with Islamic Sharia, the fostering of customary life through the application of Islamic Sharia in traditional life as regulated by Aceh's Qanun, the customary judiciary in Aceh, and the enforcement of sanctions based on the Qanun Jinayat, particularly related to the crime of zina.